PENILAIAN KINERJA KEUANGAN PERUSAHAAN PELAYARAN (Studi Pada Perusahaan Pelayaran yang Tercatat di Bursa Efek Indonesia) - Kurnia Wijaya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Sea transportation network is an important industry for maritime country such as Indonesia. However, Indonesian shipping industry is hampered by global problems, especially due to a decline in coal business and world oil prices. This descriptive-quantitative study aims to analyze the financial performance of shipping companies listed in the Indonesia Stock Exchange (IDX) using financial ratios. The data of this study are from the period of 2014 to 2016, which are in forms of documentation of annual financial statements of shipping companies listed on the IDX. The sample of this research consists of PT. Pelayaran Nasional Bina Buana Raya Tbk., PT. Mitrabahtera Segara Sejati Tbk., PT. Samudera Indonesia Tbk., and PT. Wintermar Offshore Marine Tbk. The financial ratios that are used in this study are liquidity, solvency, profitability, and activity ratios. The results show that the liquidity, profitability, and activity ratios from the four shipping companies are in a downward trend from year to year. Only the solvency ratio from the four shipping companies that shows a relative improvement during 2014-2016. PT. Mitrabahtera Segara Sejati Tbk. has a better liquidity and solvency ratio than the other three companies. Meanwhile, the profitability and activity ratio of PT. Samudera Indonesia Tbk. is the best among all sample companies.Keyword: Shipping Company, Financial Performance, Financial Ratios, Liquidity, Solvency, Profitability, and Aktivitiy